Wireless Internet: 8th International Conference, WICON 2014, Lisbon, Portugal, November 13-14, 2014, Revised Selected Papers - Mumtaz, S (Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Conference on Wireless Internet, WICON 2014, held in Lisbon, Portugal, in November 2014. The 45 revised full papers were carefully reviewed and selected from numerous submissions. The papers cover topics such as 5G mobile communications, Internet of Things (IoT), super Wi-Fi and V2V/V21.